"I see myself": Craving imagery among individuals with addictive disorders. Issue 1 (2nd January 2023) - Månsson, Viktor; Andrade, Jackie; Jayaram-Lindström, Nitya; Berman, Anne H.
Abstract: Background: : Craving has been put forward as a core feature of addictive disorders. Objective: : The present qualitative study investigated the experience of craving among individuals with addictive disorders and recent experiences of cravings. Methods: : Eleven individuals with Gambling Disorder and ten with Alcohol Use Disorder (n = 21) were recruited. A semi-structured interview explored: (1) modes of thought during craving (mental imagery or verbal thoughts), (2) craving content, (3) coping strategies and (4) craving context. Results: : The thematic analysis showed that cravings were initially dominated by imagery, with a subsequent conflict between imagery and verbal thoughts. Craving content included imagery of preparative rituals, anticipation, and sensory activation, imagery of the addictive behavior "me, there and then imagery" and anticipating that "something good will come out of it ." Some participants related to craving as a symptom of sickness, and coping with craving were through distraction, reminding oneself of negative consequences, or via sensory control: avoiding stimuli associated with the addiction. Craving contexts included typical settings of drinking or gambling and engagement of both positive and negative emotions. Alcohol craving was described as an expected relief from internal stimuli, such as anxiety or stress, whereas gambling craving was more often described as an expectancy of financial reward. Conclusions: : Craving was experienced mainly through imagery containing the preparative routines and expected outcomes. Future research and clinical practice should incorporate mode of thought in cravings to better understand its role in the maintenance of the disorders and their treatment. Supplemental data for this article is available online at https://doi.org/10.1080/10550887.2022.2058299 .